In Vivo Antimicrobial Activity of Nisin Z Against S. aureus and Polyurea Pharmadendrimer PUREG4OEI48 Against P. aeruginosa from Diabetic Foot Infections - Isa Serrano; Dalila Mil-Homens; Rita F. Pires; Vasco D. B. Bonifácio; Joana F. Guerreiro; Eva Cunha; Sofia S. Costa; Luís Tavares; Manuela Oliveira (Antibiotics)
Background/Objectives: Diabetic foot infections (DFIs) are commonly associated with frequent hospitalizations, limb amputations, and premature death due to the profile of the bacteria infecting foot ulcers. DFIs are generally colonized by a polymicrobial net of bacteria that grows in biofilms, developing an increased antimicrobial resistance to multiple antibiotics. DFI treatment is a hurdle, and the need to develop new therapies that do not promote resistance is urgent. Therefore, the antibacterial efficacy of Nisin Z (antimicrobial peptide), a core–shell polycationic polyurea pharmadendrimer (PUREG4OEI48) (antimicrobial polymer), and amlodipine (antihypertensive drug) was evaluated against S. aureus and P. aeruginosa isolated from a DFI and previously characterized. Methods: The antibacterial activity was analyzed in vitro by determining the minimal inhibitory concentration (MIC) and in vivo in a Galleria mellonella model by assessing the larvae survival and health index. Results: The results indicate that Nisin Z exhibited antibacterial activity against S. aureus in vivo, allowing larvae full survival, and no antibacterial activity against P. aeruginosa. Nisin Z may have reduced the antibacterial effectiveness of both PUREG4OEI48 and amlodipine. PUREG4OEI48 significantly increased the survival of the larvae infected with P. aeruginosa, while amlodipine showed no activity against both bacteria in vivo. Conclusions: These findings suggest that both Nisin Z and PUREG4OEI48 could potentially be used individually as adjunct treatments for mild DFIs. However, further studies are needed to confirm these findings and assess the potential toxicity and efficacy of PUREG4OEI48 in more complex models.